Differences in Self-Awareness of Students Who Attend Islamic and General Bases - Siti Khosiyah; Triana Malenita Dewi; Masayu Alifah Saznabillah; Aisyah Rizky Faradila; Idup Sapitri; Mahesa Belanti; Husna Dendara (Journal of Psychology and Social Sciences, 2024)
The study aimed to find the relationship between the self-awareness of psychology students at Raden Fatah Islamic University and Sriwijaya University, Palembang. Self-awareness can be interpreted as a person's ability to understand deeply, including strengths, weaknesses, values, and feelings. The method used is quantitative with a comparative research type by collecting data using a questionnaire, then there is an independent sample T-test. The self-awareness scale is presented in the form of a Likert scale, which is distributed through a questionnaire with four response options: Very Unsuitable (STS), Not Appropriate (TS), Appropriate (S), and Very Appropriate (SS). Favorable statement items are assessed as follows: STS is given a score of 1, TS is given a score of 2, S is given a score of 3, and SS is given a score of 4. Meanwhile, the value of unfavorable statements is given the opposite value. The research results show that the overall population data of respondents consisted of N = 50, consisting of N = 25 Sriwijaya University and N = 25 UIN Raden Fatah Palembang. Sriwijaya University mean value = 77.92, std. Deviation = 4.73392, std. Error Mean = 0.946788. Raden Fatah State Islamic University Palembang mean value = 79.72, std. Deviation = 6.90724, std. Error Mean = 1.38145. sig. value (2-tailed) = 0.288, while research = 5% or 0.05 means (0.288 > 0.05) it can be concluded that this study accepts H0 and rejects Ha. It can be concluded that there is no significant difference in self-aswers on Character Building in Students at Raden Fatah State Islamic University and Sriwijaya University Palembang.